Anti-Corruption Education Model in Islamic Universities - Firman Firman; Nurdin Kaso; Arifuddin Arifuddin; Mirnawati Mirnawati; Dodi Ilham; Abdul Rahim Karim (AL-ISHLAH: Jurnal Pendidikan, 2021)
Anti-corruption education in Islamic religious colleges aims to provide students with sufficient knowledge about the ins and outs of corruption and its eradication and instill anti-corruption values. This descriptive qualitative research with the literature study method examines various reference books, state regulations, and journals relevant to the research topic. This study captures and describes the concepts and models of anti-corruption education management in religious colleges. The student anti-corruption movement is expected to appear at the front as a driving force. Students are supported by their basic competencies: intelligence, critical thinking skills, and the courage to state the truth. This study found that there are three models of anti-corruption education at PTKI (religious universities) in Indonesia, namely 1) integrated anti-corruption education in courses, 2) integrated anti-corruption education in student activities, and 3) cultural habituation and anti-corruption character in the academic community.